Patient-Reported Outcomes Measures in Rhinoplasty: Need for Use and Implementation - Warinner, Chloe; Loyo, Myriam; Gu, Jeffrey; Wamkpah, Nneoma S.; Chi, John J.; Lindsay, Robin W. (Facial Plastic Surgery, 2023)
Patient-reported outcome metrics (PROMs) are increasingly utilized to capture data about patients' quality of life. PROMs play an important role in the value-based health care movement by providing a patient-centered metric of quality. There are many barriers to the implementation of PROMs, and widespread adoption requires buy-in from numerous stakeholders including patients, clinicians, institutions, and payers. Several validated PROMs have been utilized by facial plastic surgeons to measure both functional and aesthetic outcomes among rhinoplasty patients. These PROMs can help clinicians and rhinoplasty patients participate in shared decision making (SDM), a process via which clinicians and patients arrive at treatment decisions together through a patient-centered approach. However, widespread adoption of PROMs and SDM has not yet been achieved. Further work should focus on overcoming barriers to implementation and engaging key stakeholders to increase the utilization of PROMs in rhinoplasty.
Keywords: PROM; patient-reported outcome metrics; rhinoplasty; shared decision making; value-based health care